Respostas
respondido por:
4
Olá Yale
u = (a+1, 2)
v = (-3 , a)
produto escalar u.v
u.v = u1*v1 + u2*v2
u.v = (a + 1)*(-3) + 2*(a) = 0
-3a - 3 + 2a = 0
-a - 3 = 0
a = -3
.
u = (a+1, 2)
v = (-3 , a)
produto escalar u.v
u.v = u1*v1 + u2*v2
u.v = (a + 1)*(-3) + 2*(a) = 0
-3a - 3 + 2a = 0
-a - 3 = 0
a = -3
.
YAle123:
Muito obrigada por responder, sua resposta ajudou muito, grata mesmo de coração.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás